Las comisarías del Santo Oficio de la Nueva España, siglos XVI-XVII - Miranda Ojeda, Pedro (Contribuciones desde Coatepec; Núm. 18 (2010), 2010)
Las comisarías del Santo Oficio de la Nueva España, siglos XVI-XVII